How to write history that people want to read - Curthoys, Ann (UNSW Press, 2009)
This practical book, drawn from decades of experience, is an indispensible guide to writing history. Aimed at all kinds of people who write history academic historians, public historians, professional historians, family historians and students of all levels the book includes a wide range of examples from many genres and styles.